Leadership și cultură organizațională: Surse de putere în organizații - Cristina MORA (Revista Transilvană de Ştiinţe Administrative, 2005)
In this article we tried to demonstrate that the organizational leadership problems are very well connected to the organizational culture ones. Organizational culture can help to the clarification of many phenomenons that appear in the organizations, can operate as brake or incentive for organizational effectiveness and the leadership play the main role in the creation and the development of organizational culture.